2004
DOI: 10.1590/s0103-90162004000400014
|View full text |Cite
|
Sign up to set email alerts
|

Acid phosphatase activity and leaf phosphorus content in soybean cultivars

Abstract: The phosphate fertilization represents the most costly fraction of soybean crop production. Efficient soybean cultivars for P absorption and utilization in soils of medium available P are highly desirable and might contribute for increasing crop production potential. Thirty two soybean [Glycine max (L.) Merr.] cultivars recommended for 'Cerrado' and differing in growth cycle (early, semi-early, semi-late, and late) were grown in a dystrophic Typic Haplustox Cerrado soil to evaluate the acid phosphatase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
2
7
1
3
Order By: Relevance
“…Previous studies have reported significant effects of P availability on soybean shoot biomass and P uptake (Raposo et al, 2004;Shujie and Yunfa, 2011;Wang et al, 2010), however we did not observe a significant relationship between soil labile P with root or shoot P uptake. Labile P values in the spring at four of the sites indicate low levels of P (24-42 mg P kg À1 ) but this was not reflected in the shoot and root weight or plant P concentrations.…”
Section: Soil P Availability and Contribution To Plant Growthcontrasting
confidence: 99%
“…Previous studies have reported significant effects of P availability on soybean shoot biomass and P uptake (Raposo et al, 2004;Shujie and Yunfa, 2011;Wang et al, 2010), however we did not observe a significant relationship between soil labile P with root or shoot P uptake. Labile P values in the spring at four of the sites indicate low levels of P (24-42 mg P kg À1 ) but this was not reflected in the shoot and root weight or plant P concentrations.…”
Section: Soil P Availability and Contribution To Plant Growthcontrasting
confidence: 99%
“…Leaf acid phosphatase activity correlated negatively with P content in leaves (r = -0.73; Fig 5), which is similar to those reported for soybean in Brazil (Raposo et al 2004) and groundnut in India (Naga Madhuri et al 2017). The study also identified 3 groundnut genotypes that not only had low leaf acid phosphatase activity but also accumulated higher leaf P content.…”
Section: Resultssupporting
confidence: 85%
“…The lower concentration of P in leaves that received the highest level of P is due to the higher dry matter accumulation of leaves, thus diluting the concentration of the element in the total of leaves produced, a fact confirmed by the higher production of dry matter of leaves in the plots with the control level in relation to the plots treated with the restrictive level (Figure 1). For different soybean maturity groups grown in a RedYellow Distrophic Oxisol, with medium content of P, Raposo et al (2004) reported a negative relationship between P concentration in leaves and biomass produced, emphasizing the effect of nutrient dilution. P content in leaves was determined by the product of the leaf P concentration and dry matter of leaves, 2.78 and 3.42 g P, respectively, for plots with restrictive and control levels, that is, with a decrease of 18.71% in P content in the plots treated with restrictive level, confirming the greater accumulation of the nutrient in the leaves, accompanied by increased production of dry matter.…”
Section: Methodsmentioning
confidence: 92%